Comparison and Estimation of Surface Albedo of Various Levels of Land use by SEBAL and METRIC Methods - Mehdi Asadi; Khalil Valizadeh khamran; Mohammad Baaghdeh; Hamed Adab (تحقیقات کاربردی علوم جغرافیایی)
Using Landsat satellite images taken in 2015/08/10 and also SEBAL and metric methods, surface albedo amounts for various land uses in the northern half of the Ardabil province was estimated. ENVI4.8 and ArcGIS10.3 softwares were also used. To determine the type of usage of different levels, the maximum likelihood algorithm classification method was used with Kappa coefficient of 86.14% and overall accuracy of 92.63%. The results indicated that the water levels with the mean value of 0.93 and 0.414, respectively, had the least amount of albedo in SEBAL and METRIC methods. Also, based on the results obtained from SEBAL and METRIC methods the city albedo is about 0.313 and 0.278 respectively.  These values are the highest levels of albedo among Land use levels. In this study, the amount of albedo in rangelands was determined to be between 0.183 to 0.266 in the SEBAL method and between 0.237 and 0.265 in METRIC method. The amount of albedo was also examined in agricultural (0.240 based on SEBAL method and 0.247 based on METRIC method) and forest lands (0.149 based on SEBAL method and 0.225 based on METRIC method). Finally, according to the results of Albedo values based on SEBAL and METRIC methods, it was concluded that due to the difference in net energy received at different levels, it is possible to estimate the level of albedo levels, which is very effective in estimating evapotranspiration by remote sensing methods.